IMPLEMENTASI FUZZY TIME SERIES LOGIKA LEE UNTUK PERAMALAN INFLASI DI INDONESIA - Aulia Fitri Fireza; Defri Ahmad (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Inflation is a process of continuous increase in the price of goods or an economic situation that shows a tendency to increase the price level in general. One way to control inflation is to use forecasting. Forecasting is an activity to predict future events. Related to forecasting, the method that can be used in forecasting inflation time series data in Indonesia is the fuzzy time series method of Lee's logic. This study aims to apply Lee's Fuzzy Time Series method in forecasting inflation in Indonesia in the period January 2014 to December 2022. The forecasting results of the method are then measured using MAE and MAPE. In this study, the results of inflation forecasting in Indonesia follow the pattern of actual data. Meanwhile, the forecasting accuracy value obtained a MAE value of 0.0043 and a MAPE value of 11.7%, so that inflation forecasting in Indonesia using the Fuzzy Time Series Lee method based on MAPE criteria is good